Democracy and development: the case of the Republic of Korea (2013)
The miracle of the Han River as South Korea's development is known decades ago, resulted in one of the most prosperous economies in Asia and perhaps the world. However, if you study your case, you can understand the reason for such a miracle, an expression that by then will have become effective for the reality of the events. This document aims to publicize the process that South Korea faced from the separation of the Korean peninsula, and how the adoption of an authoritarian political system led to the achievement of important economic achievements, although with a great social cost. Finally, a comparison with the Colombian case will show the importance of developing a government plan with a long-term focus, as well as investing in education.